Optimization of Pregnancy Exercise Education on Knowledge of Perineal Rupture Incidents During Health Crisis at Antang Perumnas Community Health Center in 2024 (International Forum of Researchers and Lecturers, 2025)
Childbirth is often accompanied by perineal tears, also known as perineal rupture, which can cause significant bleeding. Perineal tears occur due to rupture of the tissues in the birth canal during the delivery process. This condition can lead to postpartum complications and negatively affect the mother’s recovery. One preventive measure is to strengthen and maintain the elasticity of the perineum through pregnancy exercises. Pregnancy exercises can improve blood circulation, enhance muscle flexibility, and prepare the body for the birthing process, thereby reducing the risk of perineal rupture. This study aimed to determine the effectiveness of optimizing pregnancy exercise education for pregnant women in improving their knowledge regarding perineal rupture incidents during health crisis situations at the Antang Perumnas Community Health Center in 2024. The research employed an observational analytic method with a quantitative approach, using a cross-sectional design to assess the relationship between the provision of pregnancy exercise education and the knowledge level of pregnant women. Data were collected through questionnaires distributed to participants, followed by statistical analysis. The results showed that pregnancy exercise education had a significant effect on pregnant women’s knowledge of perineal rupture during health crisis situations. Statistical analysis revealed a p-value of 0.000, which is less than 0.05, indicating that the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected. This finding suggests that education on pregnancy exercises can substantially improve awareness and understanding of perineal rupture prevention. In conclusion, pregnancy exercise education is an effective intervention to increase pregnant women’s knowledge and awareness about preventing perineal rupture, especially in health crisis conditions. Implementing regular education sessions in community health centers may contribute to reducing the prevalence of perineal tears and improving maternal health outcomes.